Putative targets of virus-induced teleost fish homologues of mammalian immune-relevant microribonucleic acids - Bela-ong, Dennis B. (Animo Repository, 2016)
Background: Microribonucleic acids or microRNAs (miRNAs) are short (18-22 nucleotides) endogenous RNAs that potently regulate the expression of a wide spectrum of genes through the RNA interference mechanism (RNAi). In RNAi, miRNAs repress the translation of target mRNAs or mediate mRNA degradation following interaction with the target 3’-untranslated region (UTR). RNAi has been implicated in the regulation of almost all cellular processes, including host-pathogen interactions. Our previous microarray-based miRNA expression profiling revealed that infection of a salmonid fish with a rhabdovirus induced the expression of several miRNAs in the liver. These miRNAs are homologous to mammalian miRNAs shown to regulate genes involved in immune responses, whereas the roles of these fish miRNAs are yet unclear. Here, we aimed to further investigate the potential interactions of these virus- induced fish miRNAs with mRNAs that may be relevant to host-virus cross-talk. Methodology: To identify potential target mRNAs of 8 of the most highly expressed rhabdovirus-induced miRNAs, we analysed microarray-based mRNA profiles (obtained simultaneously with miRNA expression profiles of the same liver samples). FASTA nucleotide sequences of negatively regulated miRNAs were obtained through NCBI Batch BLAST. The nucleotide sequences were aligned against the Salmon protein database (GCF_000233375.1 version 2) using Local BLASTx (BLAST 2.2.6) to determine identities of presumptive target expressed sequence tags-mRNA. Resulting XML files were further processed for annotation, gene ontology, and inclusive pathways using BLAST2GO 3.1. Additionally, putative targets of the upregulated miRNAs in genomes of salmonid-infecting viruses were predicted using RNA hybrid. Major findings: Analysis of the co-expressed mRNA profiles in the same samples and comparison with miRNA expression data revealed negatively correlated miRNA-mRNA pairs, suggesting miRNA-target relationship. The downregulated mRNAs mapped to more than 80% of the EST-mRNAs in the salmon database. Subsequently, we investigated the potential roles during virus infection of the downregulated mRNAs (and that of their protein products) by analyzing the signaling pathways enriched by the target genes of upregulated miRNAs. Gene-ontology-based annotation and functional/pathway enrichment analysis of inversely correlated mRNAs showed that they are encoded by genes whose protein products were most frequently associated with the cell cycle, immune-relevant pathways, and metabolic pathways known to be altered by virus infections in humans. Finally, analysis of genomes of some salmonid-infecting viruses showed potential targets for rhabdovirus- induced miRNAs, suggesting direct antiviral activities. Conclusions/Perspectives: Our results highlight pathways essential to antiviral defense, besides key miRNAs that modulate these processes. Collectively, our data provide a snapshot of host gene expression dynamics induced by fish rhabdovirus infection and mediated by miRNAs that orchestrate the activities of key regulators of host-virus interactions by their convergent action on multiple target genes involved in these processes. Results will further our understanding of cellular processes that are altered in response to rhabdovirus infection in fish, providing a context for future experimental analyses and functional studies, while miRNA signatures during infection may be used as biomarkers of immune responses in fish and generally, in vertebrates.